Maneuver Control System for Collision Avoidance Based on Experimental Study - Kusnindar Priohutomo; Agus Achmad Masroeri; Chandra Permana (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2018)
Autopilot mode in the ship navigation system is intended to assist the work of the captain in controlling the ship, but the autopilot mode still has some disadvantages such as in the case of maneuvers to avoid collisions. Many studies on design of anti-collision design. But almost all use a numerical approach. In this paper will be discussed the design of maneuver controls that will be used on the ship model to avoid the ship from the collision. Where within the control system there are several sensors, including ultrasonic sensors, gyro sensors and Qualysis cameras. From ship model testing conducted, the design of maneuver control proved able to avoid the ship from the occurrence of collisions. Minimum distance of ship and obstacle at 250 m distance is 34,17 m, at a distance of 200 m is 13,46 m while at a distance of 150 m is 13,36 m.